Identifikasi Faktor-Faktor Penyebab Anak Putus Sekolah di Desa Railor Kecamatan Malaka Tengah Kabupaten Malaka - Oslianus Seran Nahak; Jeferson Tanesab (SOKO GURU: Jurnal Ilmu Pendidikan, 2021)
Identification of Factors Causing Out-of-School Children in Railor Village, Central Malacca District, Malacca Regency". This study aims to: Identify the factors that cause children to drop out of school in Railor Village, Central Malacca District, Malacca Regency.The research method used is a qualitative approach and the type of research uses the case study method with data collection techniques through observation, interviews and ducumentation. The results showed that the factors that caused children to drop out of school in Railor Village as follows: 1) causative factors originating from within the child himself. 2) factors that come from outside the child that cause the child to drop out of school. Based on the results of the study, the researcher gave the following suggestions: (1) The Malacca District Education Office seems to have to follow up more on the phenomenon of elementary school (SD), Junior High School (SMP), High School (SMA) students who drop out of school (2) For the parents concerned, it seems that they should pay more attention to the child (3) The Head of the RT / RW around the student's residence should be able to collect data on residents who have dropped out of school.